Imbalanced learning in land cover classification - Douzas, Georgios (2019)
Douzas, G., Bacao, F., Fonseca, J., & Khudinyan, M. (2019). Imbalanced learning in land cover classification: Improving minority classes' prediction accuracy using the geometric SMOTE algorithm. Remote Sensing, 11(24), [3040]. https://doi.org/10.3390/rs11243040